Case Report: Therapeutic Response to Chemo-Immunotherapy in an Advanced Large Cell Lung Carcinoma Patient With Low Values of Multiple Predictive Biomarkers - Wang, Guihua; Chai, Qin; Xiao, Yajie; Peng, Wenying; Teng, Miao; Wang, Jingyi; Lin, Hanqing; Su, Xiaofan; Wu, Lin (Frontiers in Immunology, 2021)
Immune checkpoint inhibitors have revolutionized the treatments of lung cancers, and multiple predictive biomarkers alone or in combination help clinicians with the appropriate therapeutic selections. Recently, chemo-immunotherapy has been recommended for treating advanced non-small cell lung cancers in patients without driver mutations. However, the clinical relevance of predictive biomarkers and the treatment efficacy of chemo-immunotherapy in large cell lung carcinoma (LCLC) remain unclear. Here, we reported a rare case of LCLC with none driver gene mutations and low values of multiple predictive biomarkers. These biomarkers included a low PD-L1 expression of 5–10%, a low tumor mutational burden (TMB) of 2.5 muts/mb, a low CD8(+) tumor-infiltrating lymphocyte density of 147.91 psc/mm². After one-cycle chemotherapy, the patient progressed rapidly and then was switched to pembrolizumab combining paclitaxel plus cisplatin. Interestingly, he achieved a partial response after two cycles of chemo-immunotherapy, showing multiple lymph nodes obviously shrunk on CT scan, and other clinical symptoms were relieved when compared with the baseline findings. After five cycles of chemo-immunotherapy, this advanced patient still benefited and was changed to maintenance immunotherapy monotherapy. This case suggests that chemo-immunotherapy may provide an effective therapeutic option for those LCLC patients with low values of multiple predictive biomarkers, particularly for those who progressed from first-line classical treatments.